Designing an Android-Based Educational Game for Fruit Recognition in Seruni Pertiwi Preschool - Dasril; Rinto Suppa; Andi Hasjidil (Ceddi Journal of Education, 2023)
The objective of this research is to design and develop an Android-based educational game for fruit recognition in Seruni Pertiwi Preschool. The educational game application consists of a main menu, fruit menu, and tree menu. The fruit menu includes various fruit options such as bananas, papayas, apples, grapes, oranges, pineapples, watermelons, durians, rambutans, and strawberries. The research methodology employed in this thesis includes data and information collection, system design, software requirement analysis, interface design, coding, testing, and implementation. The Unity 3D engine is utilized for designing the educational game application. Based on the conducted testing, the following conclusions can be drawn: the developed educational game is free from errors based on the black-box testing results. The research findings indicate that the average validation score from user feedback, ranging from user 1 to user 10, is 4.6, which indicates a high level of agreement with the system assessment, falling under the category of "strongly agree".